Climate change fingerprints in recent European plant phenology. (8th February 2020) - Menzel, Annette; Yuan, Ye; Matiu, Michael; Sparks, Tim; Scheifinger, Helfried; Gehrig, Regula; Estrella, Nicole
Abstract: A paper published in Global Change Biology in 2006 revealed that phenological responses in 1971–2000 matched the warming pattern in Europe, but a lack of chilling and adaptation in farming may have reversed these findings. Therefore, for 1951–2018 in a corresponding data set, we determined changes as linear trends and analysed their variation by plant traits/groups, across season and time as well as their attribution to warming following IPCC methodology. Although spring and summer phases in wild plants advanced less (maximum advances in 1978–2007), more ( 90%) and more significant ( 60%) negative trends were present, being stronger in early spring, at higher elevations, but smaller for nonwoody insect‐pollinated species. These trends were strongly attributable to winter and spring warming. Findings for crop spring phases were similar, but were less pronounced. There were clearer and attributable signs for a delayed senescence in response to winter and spring warming. These changes resulted in a longer growing season, but a constant generative period in wild plants and a shortened one in agricultural crops. Phenology determined by farmers' decisions differed noticeably from the purely climatic driven phases with smaller percentages of advancing ( 75%) trends, but farmers' spring activities were the only group with reinforced advancement, suggesting adaptation. Trends in farmers' spring and summer activities were very likely/likely associated with the warming pattern. In contrast, the advance in autumn farming phases was significantly associated with below average summer warming. Thus, under ongoing climate change with decreased chilling the advancing phenology in spring and summer is still attributable to warming; even the farmers' activities in these seasons mirror, to a lesser extent, the warming. Our findings point to adaptation to climate change in agriculture and reveal diverse implications for terrestrial ecosystems; the strong attribution supports the necessary mediation of warming impacts to the general public. Abstract : We detected attributable fingerprints of climate change in European plant phenology by investigating 97, 000 time series of multiple agricultural and wild species as well as farming activities. The mean advance in spring and summer was −0.24 days/year, but varied with trait, land use, season and site. Trends halved after 1980 probably by a lack of chilling and/or reduced forcing. Yet, advances in spring, even in agriculture, as well as delayed autumn phases were (very) likely to match the warming pattern. Nature may profit from longer growing seasons, whereas farming seasons and crop generative periods are shortened.